Induction of vasodilation by hydrogen peroxide and its application in exercise science - Sung, D. J.; So, W. Y.; Ryu, H. Y.; An, H. S.; Cha, K. S. (Biology of Sport, 2012)
Regular exercise or physical activity benefits the cardiovascular system, lowers mortality and morbidity, and is a particularly important factor for maintaining the health of blood vessels by improving the function of endothelial cells. Shear stress and increased metabolic rate caused by exercise induce vasodilation by generating endothelium-derived relaxing factors (EDRF) such as nitric oxide. In addition, some studies suggest that vasodilation is also induced by endothelium-derived hyperpolarizing factors (EDHF) and substances such as H2O2. Thus, we undertook this study to show that reactive oxygen species such as H2O2 that have not previously been investigated in the field of exercise science may induce vasodilation and an increase in blood pressure, and to provide information for application in the field of exercise science. In this review, we discuss reports on H2O2 published in the fields of basic science and exercise science while focusing on vasodilation induced by H2O2. H2O2 induces vasodilation by simultaneously increasing endothelial NOS (eNOS) and directly activating the Ca2+- activated K+ channels of vascular smooth muscle cells. A novel study should be conducted in the field of H2O2 as a factor of vasodilation via increased metabolic rate during exercise.